Efforts To Improve Mathematics Learning Outcomes Through The Application Of The Problem Based Learning Model In Class V Semester 2 At MI Muh Nogosari Kulon Progo Academic Year 2022/2023 - Fazah, Mirza (Journal of Social Science and Economics, 2023)
In order to improve the quality of the learning process and outcomes of mathematics subjects, it is deemed necessary to apply a problem-based learning model. The problem-based learning model is a learning model that is based on many problems that require authentic investigation, namely investigations that require real investigation of real problems. The problems used are problems that are familiar to students' daily lives. This research uses a Classroom Action Research (PTK) design. Classroom Action Research is research that examines student learning activities by providing actions that are deliberately created. The activity of observing an object to obtain data that is useful for the common good. Implementation of PTK actions is carried out in several periods or cycles. The implementation from cycle 1 to cycle 2 has improved. This research shows that student learning outcomes have improved after taking action. The percentage of students who have not completed has decreased from cycle 1 to cycle 2 (from 75% to 0%. The percentage of students who have completed has increased from cycle 1 to cycle 2 (from 25% to 100%).